The Legal Principle of Appearance - Falzea, Angelo (2006)
This article presents a detailed and analytical view of the legal principle of appearance, examining its evolution and its impact on modern law and, in particular, on Italian doctrine. Appearance, the author argues, is a complex phenomenon that presents itself as a factual situation that manifests as real a legal situation that is not in fact real. In this sense, appearance as a legal principle includes the objective perception of the legitimacy of a person to perform certain acts, which is supported by objective circumstances, but which can also coexist with subjective elements, such as good faith. Thus, it is mentioned that this principle aims to protect the interest of a third party who, acting in good faith, has been deceived by a situation of appearance, by ensuring that the legal effects linked to that interest remain valid. The author concludes by pointing out that, in spite of the different opinions found in Italian doctrine and case law regarding this principle, its relevance in the Italian legal system has been confirmed by its application in concrete cases.